2015
DOI: 10.1111/are.12785
|View full text |Cite
|
Sign up to set email alerts
|

The recruitment of scallops (and beyond) by two different artificial collectors (Gulf of Taranto, Mediterranean Sea)

Abstract: This study provides for the first time an evaluation\ud of the natural availability of scallop seeds along\ud the coastal area of Taranto (Mediterranean Sea,\ud Southern Italy). To select the best artificial collectors\ud to harvest scallop seeds in this area, cylindrical\ud collectors (Cyl) were compared to traditional\ud ‘Japanese-style onion bags’ (Bag) across three sites.\ud Scallops represented 26.6% of total bivalve recruitment\ud among all collectors (782 ± 331 ind. m-2, \ud The most recruited scallops … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…A previous study determined the natural availability of scallops spat in the Mar Grande of Taranto (Ionian Sea, Mediterranean Sea), identifying the best collection site and confirming the efficiency of traditional collectors [28].…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…A previous study determined the natural availability of scallops spat in the Mar Grande of Taranto (Ionian Sea, Mediterranean Sea), identifying the best collection site and confirming the efficiency of traditional collectors [28].…”
Section: Introductionmentioning
confidence: 77%
“…They are a high-value seafood [28,37], for which the market demand is so strong that existing supplies are inadequate. [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and the high market value of F. glaber , comparable to that of the depleted wild Pilgrim’ scallop ( Pecten jacobeus ), make this species of great interest for the development of scallop culture (Marčeta et al, 2016). Prato et al (2015), demonstrated that wild F. glaber spat in the Ionian waters is easy to collect on artificial substrates, where scallop juveniles have shown to be the most frequent and abundant of all settled bivalves. In addition, Tsiotisios et al (2016) reported a high settlement density of F. glaber from the beginning of May to the end of August in the northwestern Amvrakikos Gulf (Ionian Sea, Greece).…”
Section: Introductionmentioning
confidence: 99%
“…The labor intensiveness of this technology makes it unprofitable both in Russia [4] and in Europe [5]. The studies aimed at optimizing the cultivation process [6][7][8][9][10][11][12][13] and reducing the number of scallop reseeding operations [14] have been conducted for a long time.…”
Section: Introduction mentioning
confidence: 99%